PENYELESAIAN NILAI PERIWAYAT MUDALLIS DAN MUKHTALAT - Harahap, Taufiqurrahman; Hasanah, Dina; Alfajar, M.Khalid (Jurnal Ushuluddin, 2023)
This study examines the resolution methods for evaluating mudallis and mukhtalat narrators in the science of hadith. A mudallis refers to a narrator who conceals flaws in the chain of transmission using various techniques, while a mukhtalat denotes a narrator whose memory has deteriorated, impacting the reliability of their narrations. These categories significantly affect the quality of hadith. This research employs a qualitative approach through the analysis of classical and contemporary hadith literature to identify methods for validating narrations from these types of narrators. The findings reveal three main steps in assessing mudallis and mukhtalat narrators: (1) analyzing the chain of transmission to detect indications of tadlis or memory alteration, (2) evaluating narrations based on the opinions of scholars of jarh wa ta’dil, and (3) applying hadith criticism principles to measure the validity of narrations. This study highlights the importance of caution when accepting narrations from mudallis and mukhtalat narrators to preserve the authenticity of hadith. Keywords: Mudallis, Mukhtalat, Hadith Criticism, Jarh wa Ta’dil, Chain Validation.